Notas sobre a Arte de grammatica, latina, portugueza, benedictina (Lisboa, 1636) de Frutuoso Pereira - Ponce de León Romeo, Rogelio (2014)
This paper analyzes several aspects of frutuoso Pereira's work Arte de gramatica, latina, portugueza, benedictina (Lisboa, 1636). Mainly issues that have to do with the textual tradition and authorship, as well as issues related to the Portuguese pedagogical context of the first half of the seventeenth century. It also analyzes the framing of the Arte de gramatica in the grammar current trends at the time, specifically, in the rationalist grammar and in the school grammar.